Proposed upgrading down syndrome kids’centre for Persatuan Sindrom Down Malaysia at 79, Lingkungan U-Thant, 55000 Kuala Lumpur. / Siti Nur Amanina Sukarno - Sukarno, Siti Nur Amanina (Faculty of Architecture, Planning and Surveying, 2010)
Every design stage should be completed thoroughly to ensure a successful down syndrome kids’ centre design. The design objective of the project, site suitability, and the project requirements are analyzed to avoid lack of understanding that will lead to bad design. Other than that, the determining of concept and images play important parts in design as they act as guideline to the design proposal. If these factors are being neglected, there are possibilities for the down syndrome kids’ centre to be ignored by the public and left abandoned. In order to make sure a perfect design planning, the basic design aspects such as the comfortability of each space, ergonomics and anthropometries, and psychological factors must be taken into consideration. At the same time, all of the data collections should be implemented in the design process so that the concept and image of excitement interior will be reflected in the design. Through the proposed interior design of down syndrome kids’ centre for Persatuan Sindrom Down Malaysia, it is hoped that Persatuan Sindrom Down Malaysia will achieve its objective which is to give the children education and speciality in their life.